2014
DOI: 10.1016/j.biopsych.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Mood Balance in Depression: Ketamine Reverses Deficit in Dopamine-Dependent Synaptic Plasticity

Abstract: Background One of the most novel and exciting findings in major depressive disorder research over the last decade is the discovery of the fast-acting and long-lasting antidepressant effects of ketamine. Indeed, the therapeutic effects of classic antidepressant such as SSRIs require a month or longer to be expressed, with about a third of MDD patients resistant to treatment. Clinical studies have shown that low dose of ketamine exhibits fast-acting relatively sustained antidepressant action even in treatment-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
160
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 49 publications
20
160
0
3
Order By: Relevance
“…In animal models of MDDs, in which anhedonia is a core symptom, a decrease in DA neuron activity in the VTA has been described by our group (Belujon and Grace, 2014;Chang and Grace, 2014) and others (Tye et al, 2013). Indeed, we have shown previously in the CMS model (Chang and Grace, 2014) a decrease in DA activity in the VTA, as well as an increase in immobility time, in the FST.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In animal models of MDDs, in which anhedonia is a core symptom, a decrease in DA neuron activity in the VTA has been described by our group (Belujon and Grace, 2014;Chang and Grace, 2014) and others (Tye et al, 2013). Indeed, we have shown previously in the CMS model (Chang and Grace, 2014) a decrease in DA activity in the VTA, as well as an increase in immobility time, in the FST.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, we have shown previously in the CMS model (Chang and Grace, 2014) a decrease in DA activity in the VTA, as well as an increase in immobility time, in the FST. Moreover, in the learned helplessness model, a decrease in DA activity, as well as failure to escape, has been described (Belujon and Grace, 2014). Using optogenetic techniques, Tye et al (2013) have observed in CMS rats a robust increase in kick frequency in the FST following activation of DA neurons in the VTA, which was not time locked to the light pulses, suggesting a role for dopaminergic tone, rather than bursting activity, in this behavior.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mechanistic studies in animals show that ketamine rapidly enhances synaptic plasticity at the level of prefrontal cortical neurons (Li et al, 2010(Li et al, , 2011, and is able to rapidly reverse stress-induced dendritic atrophy and behavioral depression in a brain-derived neurotrophic factor (BDNF)-dependent manner (Li et al, 2011;Liu et al, 2012). A recent study found that ketamine reversed deficit dopamine signaling in a learned helplessness model of depression and normalized synaptic plasticity within the nucleus accumbens (indexed by long-term potentiation) via activation of dopamine D1 receptors (Belujon and Grace, 2014). Chronic and/or uncontrollable forms of stress are known to reduce dopamine signaling at the level of the ventral tegmental area (VTA) and striatum (Cabib and Puglisi-Allegra, 2012), and these data suggest that ketamine may alleviate depressive symptoms, at least in part, via modulation of dopamine signaling.…”
Section: Discussionmentioning
confidence: 99%